Etika Jurnalisme di Era Digital: Tantangan dan Strategi dalam Menghadapi Hoaks dan Disinformasi - nur aliah (JURNALISTIK DAN MEDIA, 2025)
This proposal discusses the practice of journalistic ethics and strategies implemented by traditional media in Indonesia in facing the challenges of spreading hoaxes and disinformation. This study focuses on three traditional media, namely Mediasulsel, Kompas TV, and TVRI. The development of information and communication technology, especially the internet, has brought about major changes in the media landscape. The digital era has given birth to new media platforms that allow faster and easier access to information. However, behind the rapid development of digital media, there are new challenges that need to be overcome, namely the spread of hoaxes and disinformation. Hoaxes and disinformation are false information that is deliberately created to mislead the public. This study aims to describe the practice of journalistic ethics implemented by traditional media in Indonesia, especially Mediasulsel, Kompas TV, and TVRI in facing the challenges of spreading hoaxes and disinformation, and to identify strategies implemented by traditional media in countering hoaxes and disinformation. This study uses a qualitative approach with data collection techniques in the form of interviews, documentation, and observation. Data is analyzed thematically and content to identify the main themes and messages contained in the documents collected. The results of the study show that the three traditional media have strict verification practices and emphasize the importance of selecting competent sources. They also agree that mainstream media has an important role in clarifying information circulating on social media. The strategies implemented to build public trust include verifying information, selecting competent sources, and maintaining journalistic ethics. This study concludes that traditional media have journalistic ethics practices and effective strategies in countering hoaxes and disinformation. Despite facing challenges such as pressure to produce fast and viral news, fast and wide distribution of information, and lack of digital literacy in society.